2010
DOI: 10.1007/s11999-010-1472-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Margins and Local Control in Resection of Sacral Chordomas

Abstract: Background The treatment of choice in sacral chordoma is surgical resection, although the risk of local recurrence and metastasis remains high. The quality of surgical margins obtained at initial surgery is the primary factor to improve survival reducing the risk of local recurrence, but proximal sacral resections are associated with substantial perioperative morbidity. Questions/purposes We considered survivorship related to local recurrence in terms of surgical margins, level of resection, and previous surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 46 publications
13
152
1
6
Order By: Relevance
“…The conditional 5-year survival of patients who received an inadequate margin resection showed the lowest survival probability during the third and fourth years postoperatively, which indicated that the effect of the surgical margin on conditional 5-year survival was the greatest between 3 and 4 years after surgery. Despite a similar trend of the surgical margin and previous surgery in conditional survival over time, an inadequate margin and previous surgery before referral continued to have a lower 5-year conditional survival, which is consistent with previous studies demonstrating that the surgical margin is an important predictor of survival [9,23,26,34,38,42]. The surgical margin is the main predictor factor for local control and disease-free survival [3,11,24,44].…”
Section: Figsupporting
confidence: 86%
“…The conditional 5-year survival of patients who received an inadequate margin resection showed the lowest survival probability during the third and fourth years postoperatively, which indicated that the effect of the surgical margin on conditional 5-year survival was the greatest between 3 and 4 years after surgery. Despite a similar trend of the surgical margin and previous surgery in conditional survival over time, an inadequate margin and previous surgery before referral continued to have a lower 5-year conditional survival, which is consistent with previous studies demonstrating that the surgical margin is an important predictor of survival [9,23,26,34,38,42]. The surgical margin is the main predictor factor for local control and disease-free survival [3,11,24,44].…”
Section: Figsupporting
confidence: 86%
“…Currently, there is a paucity of studies reporting on patientreported outcomes after treatment for sacral tumors. Studies that do address these outcomes use different tools and use tools that are not completed by the patient, making institutional comparisons increasingly difficult [13,14,19,23,25]. We found that, when comparing patient-reported outcomes based on the sacral nerve roots that were sacrificed, mental and physical health decreased when S3 was bilaterally sacrificed.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies focus on the crucial oncological outcomes but only briefly address the results of, often objective, functional outcome measures [13,14,23]. Patient-reported outcomes are becoming increasingly important in the determination of treatment success.…”
Section: Introductionmentioning
confidence: 99%
“…This study reveals a higher-than-expected risk of sacral insufficiency fracture following radiotherapy when compared to past studies with fracture rates of 6% to 8% [2,11]. Nearly half of the patients in the study developed insufficiency fractures, and the proportion was even higher in patients with high sacrectomy.…”
Section: Beth Israel Deaconess Medical Centermentioning
confidence: 38%
“…Since the authors were specifically searching for insufficiency fractures, they likely discovered more patients with this complication than did earlier reports that relied on the initial radiology report [2,11]. It is important for radiologists and surgeons to be aware of this complication in order to interpret the imaging scans correctly, which can guide the correct treatment.…”
Section: Beth Israel Deaconess Medical Centermentioning
confidence: 99%